Ecological footprint in Bangladesh: Identifying the intensity of economic complexity and natural resources - Md. Golam Kibria (Heliyon, 2023)
Recent years have seen a spike in the number of academics utilizing the ecological footprint as a stand-in for environmental depletion because of its extensive nature and its ability to capture the worsening of the ecosystem. Thus, this article brings a new effort to analyze the effect of Bangladesh's economic complexity and natural resources on its ecological footprint over a long period, from 1995 to 2018. Using a nonlinear autoregressive distributed lag (NARDL) model, this paper suggests that a more complex economy has a significantly positive effect on ecological footprint over the long term. If the economy is simplified, it has less impact on the environment. For Bangladesh, an increase in economic complexity of 1 unit leads to an ecological footprint increase of 0.13 units, while a drop in economic complexity of 1% causes an ecological footprint decrease of 0.41%. Results also demonstrate that both positive and negative changes in natural resources contribute to rises in environmental quality in Bangladesh, which negatively influences the country's ecological footprint. Quantitatively, a 1% increase in natural resources reduces the ecological footprint by 0.14%, whereas a 1% decrease in resources has the opposite effect, reducing it by 0.59%. In addition, an asymmetric Granger causality test confirms the existence of a unidirectional causal link from ecological footprint to a positive partial sum of natural resources and from a negative partial sum of natural resources to ecological footprint. Finally, the findings point to a two-way causal relationship between the size of an economy's ecological footprint and the complexity of its economy. Policymakers should boost technological advances and lessen operational costs by adopting an innovative Research and development framework and devoting more cash to natural resource policies that promote an adaptable ecological footprint.